Introducing Math Concepts At An Early Age: Collaborative Stimulation - Feri Faila Sufa; Budi Setiawan (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Early childhood education is considered very strategic in human development. This is because early childhood education provides a foothold in further education. Including in mathematics education which is needed from an early age. This article aims to describe the benefits of local wisdom around children's environment in introducing math concepts through collaboration during a pandemic. Methodology: This research uses a child collaborative approach through descriptive analysis in two institutions with data collection methods of interviews, questionnaires, and observations. Main Findings: The results showed that the role of communication is very important between children, parents, and teachers in collaborating to stimulate the formation of mathematics through local wisdom. Novelty/Originality of this study: This research recommends that introducing math is done with real activities, encouraging children to stimulate the habit of collaboration in improving children's life skills.